2006
DOI: 10.1089/pho.2006.24.637
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Low-Level Laser Therapy in the Treatment of Temporomandibular Disorders

Abstract: Based on the results of this placebo-controlled report, LLLT is an appropriate treatment for TMD and should be considered as an alternative to other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
1
43

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(203 citation statements)
references
References 29 publications
6
153
1
43
Order By: Relevance
“…Kulekcioglu et al [11] showed that, after 15 sessions of LLLT, TMD of both myogenic and arthrogenic causes responded to therapy with a significant reduction in pain, improvement in mouth opening and lateral motion, and a diminished number of trigger points. Ç etiner et al [12] expressed similar results in 24 patients after 10 sessions of LLLT. Improved outcome of laser therapy was documented by Santos et al [19] by applying LLLT at a comparatively higher dose.…”
Section: Low Level Laser Therapy and Temporomandibular Disordersmentioning
confidence: 63%
See 1 more Smart Citation
“…Kulekcioglu et al [11] showed that, after 15 sessions of LLLT, TMD of both myogenic and arthrogenic causes responded to therapy with a significant reduction in pain, improvement in mouth opening and lateral motion, and a diminished number of trigger points. Ç etiner et al [12] expressed similar results in 24 patients after 10 sessions of LLLT. Improved outcome of laser therapy was documented by Santos et al [19] by applying LLLT at a comparatively higher dose.…”
Section: Low Level Laser Therapy and Temporomandibular Disordersmentioning
confidence: 63%
“…Some authors reported the efficacy of LLLT to be superior to placebo therapy [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and other physical therapies , while, others found no significant differences between LLLT and placebo for the measures of TMJ pain [24][25][26]. However there is an advantage of using LLLT in the treatment of TMDs as it is non-invasive, cost effective and does not have any known side effects.…”
Section: Introductionmentioning
confidence: 99%
“…results it seemed to play positive effects on muscle tissue as important injuries were not observed at group III. Furthermore, although the findings of the present study were restricted to a specific set of parameters and that optimal treatment parameters (e.g., wavelength, dosage, number of treatment sessions) have not been, so far, agreed upon (Emshorff et al; Venancio et al), previous studies have been beneficial results using Infrared wavelengths (Çetiner et al;Fikáková et al;Kato et al, 2006;Kogawa et al, 2005;Leal Júnior et al, 2008).…”
Section: Resultsmentioning
confidence: 64%
“…However, Gam et al (1993) have not shown efficiency of LLLT on musculoskeletal disorders. Therefore, considering that the biological mechanisms resulting from action of LLLT on temporomandibular joint (TMJ), clinical trials remains unclear (Çetiner et al, 2006;Fikáková et al, 2007;Gorgey et al, 2008;Tullberg et al, 2003;Venancio et al, 2005). The aim of the present study was to analyze the influence of lasertherapy and muscle relaxant on the ultrastructural features of masseter muscle under occlusal wear.…”
Section: Introductionmentioning
confidence: 93%
“…A terapia com laser de baixa intensidade (LLLT) é um tratamento não invasivo que tem mostrado ser benéfico no tratamento de dor relacionado à DTM sendo, portanto, considerado eficiente como agente terapêutico e coadjuvante no tratamento das DTM (Kulekcioglu et al, 2003;De Medeiros et al, 2005;Çetiner et al, 2006;Mcnelly et al, 2006;Medlicott e Harris, 2006;Shinozaki et al, 2006;Fikácková et al, 2007;Mazzetto et al, 2007;Carrasco et al, 2008;Shirani et al, 2009;Marini et al, 2010;Venezian et al, 2010;Mazzetto et al, 2010;Öz et al, 2010;Dostalová et al, 2012;Sattayut e Bradley et al, 2012;Salmos-Brito et al, 2013;Melchior et al, 2013;de Moares Maia et al, 2014;Ahrari et al, 2014;Herpich et al, 2015;Rodrigues et al, 2015) e no alívio de dor cervical crônica (Chow et al, 2006). Além disso, há relatos de melhora da amplitude dos movimentos mandibulares (Kulekcioglu et al, 2003;Çetiner et al, 2006;Núñez et al, 2006;Mazzetto et al, 2010;Gökçen-Röhlig et al, 2012;Ahrari et al, 2014;Rodrigues et al, 2015), da dificuldade para mastigar (Çetiner et al, 2006) e eficiência mastigatória após a LLLT (de Moraes Maia et al, 2014).…”
Section: Laserterapiaunclassified